2012
DOI: 10.1142/s0192415x12500553
|View full text |Cite
|
Sign up to set email alerts
|

Eucommia Leaf Extract (ELE) Prevents OVX-Induced Osteoporosis and Obesity in Rats

Abstract: The cortex of Eucommia ulmoides Oliver is widely used to treat kidney deficiency in traditional Chinese medicine. Its leaves have recently been reported to have anti-obesity properties in metabolic syndrome-like rat models. Due to a sharp decline in estrogen production, obesity, together with osteoporosis, are common problems in postmenopausal women. In this study, we examined the potential effect of Eucommia leaf extract (ELE) in preventing osteoporosis and obesity induced by ovariectomy (OVX). Forty-six fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…Obesity is characterized as hypertrophy and proliferation of adipocytes in white adipose tissue (WAT) [1,2]. Eucommia leaf extract (ELE) has been reported to have various bioactive properties [3][4][5][6][7][8][9][10][11], such as anti-obesity effects [6][7][8][9][10][11]. Asperuloside (ASP) is indicated as the major ingredient of ELE; it contributes to its anti-obesity effect [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is characterized as hypertrophy and proliferation of adipocytes in white adipose tissue (WAT) [1,2]. Eucommia leaf extract (ELE) has been reported to have various bioactive properties [3][4][5][6][7][8][9][10][11], such as anti-obesity effects [6][7][8][9][10][11]. Asperuloside (ASP) is indicated as the major ingredient of ELE; it contributes to its anti-obesity effect [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…The bark of E. ulmoides (Cortex Eucommia) has been traditionally used as an herbal medicine with analeptic, analgesic, sedative, antihypertensive, and diuretic effects in Japan, China, and Korea. In vitro and in vivo studies indicated that the compounds and extracts from Eucommia ulmoides have various pharmacological effects in treating hypertension [10][11][12][13], hyperlipidemia [14,15], diabetes [16], obesity [14,[17][18][19][20], osteoporosis [21][22][23][24][25][26], and lupus-like syndrome [27], and promoting neuroprotection [28,29] and immunoregulation [30]. E. ulmoides leaves and barks have the same iridoid and lignin compound components; therefore, the leaves have been used similarly as the bark, as tonic and antihypertensive.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the study of Eucommia leaf extract (ELE) has been focused on its efficacy in maintaining human health. Reports on the biogenic effectiveness of ELE ingestion have identified the following benefits: 1) antihyperlipidemic effects that reduce visceral fat and suppress elevated levels of triglyceride and cholesterol in the blood [1][2][3][4][5][6][7]; 2) effects on bone, such as preventing the onset of postmenopausal osteoporosis and promoting calcium accumulation in osteoblasts [8][9][10]; 3) antihypertensive effects that slowly decrease blood pressure by maintaining the flexibility of the blood vessels and promoting arterial smooth muscle relaxation [2,11]; 4) rapid eye movement sleep and non-rapid eye movement sleep inducing effect [12]; and 5) preventative effects on ulcerative colitis by asperuloside, one of the major components of ELE [13]. Thus, ELE promotes systemic health.…”
Section: Introductionmentioning
confidence: 99%